Connections in death - Robb, J. D. 1950-; Ericksen, Susan (New York, NY Macmillan Audio, 2019)
Homicide officer Eve Dallas investigates the death of child psychologist Dr. Rocelle Pickering's brother, a case that takes her into the underground world of tattoo parlors and strip joints to find his murderer.
Title from disc label.
Read by Susan Ericksen.
107850
Keywords: Murder -- Investigation -- Fiction; Gangs -- Fiction; Fiction -- Mystery & Detective -- Police Procedural; Homicide -- Investigation -- Fiction; Audiobooks; Detective and mystery fiction; Fiction; Novels; Thrillers (Fiction); Suspense fiction; Mystery fiction